Penentuan Aktivitas Radionuklida Alam pada Pemandian Air Panas Gunung Panjang dan Gunung Pancar di Kabupaten Bogor Jawa Barat - Zulfa, Naela Amalia; Adrial, Rico; Makmur, Murdahayu; Yahya, Mohamad Nur; Putra, Deddy Irawan Permana; Priasetyono, Yogi (Universitas Andalas, 2024)
Research has been conducted on the determination activity of natural radionuclides at hot springs in Bogor Regency, West Java. This study aimed to determine the concentration value of natural radionuclide activity in hot springs. This study used water samples taken from water samples taken from water in two different hot spring locations, namely in Gunung Panjang Hot Spring and Gunung Panjang Hot Spring. Activity concentrations were measured using an HPGe gamma spectrometer for radionuclides 238U, 232Th, and 40K. Activity concentrations for radionuclide 238U ranged from (0.13 ± 0.01) to (33.82 ± 0.24) Bq/L, for 232Th ranged from (0.08 ± 0.01) to (100.30 ± 0.01) Bq/L and 40K ranged from (0.18 ± 0.01) to (416.84 ± 0.09) Bq/L. The concentration values of 238U, 232Th, and 40K are still below the specified threshold. The activity concentration limit of radionuclides recommended by PERKA BAPETEN No. 9 Year 2009 on Intervention Against Exposure from Technologically Enhanced Naturally Occurring Radioactive Material is 1000 Bq/L for 238U and 232Th and 10,000 Bq/L for 40K.